Maladaptive mother-child interactions in mothers with remitted major depression are associated with blunted amygdala responses to child affective facial expressions - Hindi Attar, Catherine; Ridder, Neele; Stein, Jenny; Kluczniok, Dorothea; Dittrich, Katja; Jaite, Charlotte; Spengler, Stephanie; Bödecker, Katja; Poppinga, Sina; Neukel, Corinne; Schönfeld, Judith von; Herpertz, Sabine; et al. (Psychological medicine, 2025)
BackgroundMaternal depression is associated with difficulties in understanding and adequately responding to children’s emotional signals. Consequently, the interaction between mother and child is often disturbed. However, little is known about the neural correlates of these parenting difficulties. Motivated by increasing evidence of the amygdala’s important role in mediating maternal behavior, we investigated amygdala responses to child sad and happy faces in mothers with remitted major depression disorder (rMDD) relative to healthy controls.MethodsWe used the sensitivity subscale of the emotional availability scales and functional magnetic resonance imaging in 61 rMDD and 27 healthy mothers to examine the effect of maternal sensitivity on mothers’ amygdala responses to their children’s affective facial expressions.ResultsFor mothers with rMDD relative to controls, we observed decreased maternal sensitivity when interacting with their child. They also showed reduced amygdala responses to child affective faces that were associated with lower maternal sensitivity. Connectivity analysis revealed that this blunted amygdala response in rMDD mothers was functionally correlated with reduced activation in higher-order medial prefrontal areas.ConclusionsOur results contribute toward a better understanding of the detrimental effects of lifetime depression on maternal sensitivity and associated brain responses. By targeting region-specific neural activation patterns, these results are a first step toward improving the prediction, prevention, and treatment of depression-related negative effects on mother-child interaction.